Effect of different formulations of coating materials on kenaf paper - Abdullah, Hazwani Husna (2012)
Kenaf (Hibiscus cannabinus L.), is relatively new industrial crop which has been identified as an alternative sources of fiber supply in the papermaking industry in Malaysia. The hydrophilic character of cellulosic material such as paper has directed many explorations in inventing hydrophobic paper which able to stay dry at certain conditions and period after exposing to water or moisture. In this study, experimental unbleached kenaf kraft paper was prepared as substrate to produce water resistant paper by using coating method. Coating formulation consists of commercial precipitated calcium carbonate (PCC) was used as filler in addition to 20/0 w/w g, 20/0.08 w/w, 20/0.16 w/w amount to hydrophobic stearic acid (SA). Polymer latex (PL) amount at 20/0.2 w/w, 20/0.4 w/w,20/0.4 w/w and 20/0.8 w/w were also added into the coating compound to bind the filler particles present in coating formulation. The water absorptiveness of paper was measured via water contact angle and Cobb test while the observation of paper morphology was conducted by employing scanning electron microscope (SEM). The mechanical properties of the coated water resistant paper were measured in order to determine the paper strength. Hydrophobic kenaf kraft paper prepared in this study exhibited reading of water contact angle (θ) greater than 90° which indicates to almost non-wetting condition. Hydrophobic paper of formulation PL4c resulted in the highest value contact angle of 147°C. The process of dipping treatment resulted in higher water contact angle reading of the paper surface. This paper surface acquired higher hydrophobic level. However, the coated paper demonstrated decrement in mechanical strength by the increasing addition of stearic acid.